P2Y12 Receptor Antagonist, Clopidogrel, Does Not Contribute to Risk of Osteoporotic Fractures in Stroke Patients - Jørgensen, Niklas R.; Schwarz, Peter; Iversen, Helle K.; Vestergaard, Peter (Frontiers in Pharmacology, 2017)
Background: Stroke is a leading cause of mortality and morbidity. It is associated with excessive bone loss and risk of fracture in stroke patients is high. The P2Y12R antagonist and platelet inhibitor, clopidogrel, is widely used for secondary prevention after a stroke. However, recent studies have shown that clopidogrel has negative effects on bone and that long-term clopidogrel use is associated with increased fracture risk. The purpose of the current study was therefore to investigate the association of clopidogrel treatment with risk of fractures in stroke and TIA patients. Methods: The study was a cohort study including all subjects who were prescribed clopidogrel between 1996 and 2008 in Denmark (n=77,503). Age- and gender matched controls (n=232,510) were randomly selected from the background population. The study end-points were occurrence of stroke or TIA and occurrence of fracture. Clopidogrel use was primary exposure. Results: Ischemic stroke increased risk of fracture by 50% while haemorrhagic stroke and TIA increased the risk by 30%. However, after adjusting for multiple confounders only patients with ischemic stroke and haemorrhagic stroke had increased fracture risk. Clopidogrel use was not associated with increased fracture risk in subjects with ischaemic stroke or TIA. In contrast, after adjusting for multiple confounders clopidogrel treatment was associated with a 10 to 35% reduced risk of fracture. Conclusions: Patients with stroke have increased risk of osteoporotic fractures, but clopidogrel treatment does not increase fracture risk. In contrast, patients less adherent to the treatment have lower risk of fractures than non-users and patients with high adherence. However, based on the increased risk in stroke patients, clinicians should consider evaluation of bone status of these patients.